Cardiometabolic Risk and Body Composition in Youth With Down Syndrome - Magge, Sheela N. (Pediatrics, 2019)
BACKGROUND AND OBJECTIVES: Whether BMI captures adiposity and cardiometabolic risk in Down syndrome (DS), a condition associated with obesity, short stature, and altered body proportions, is not known. We compared cardiometabolic risk measures in youth with DS and typically developing matched controls. METHODS: Youth with (n = 150) and without (n = 103) DS of comparable age (10–20 years), sex, race, ethnicity, and BMI percentile underwent whole-body dual-energy X-ray absorptiometry, fasting glucose, insulin, lipids, lipoprotein particles, inflammatory factors, and when BMI percentile ≥85, an oral glucose tolerance test. RESULTS: Sixty-four percent of youth with DS had BMI percentile ≥85. Among these, no difference in glucose, insulin, or insulin resistance was detected, but prediabetes was more prevalent with DS (26.4% vs 10.3%; P = .025) after adjustment for demographics, pubertal status, and BMI z score (odds ratio = 3.2; P = .026). Among all participants, those with DS had higher low-density lipoprotein cholesterol (median 107 [interquartile range 89–128] vs 88.5 [79–103] mg/dL; P < .00005), triglycerides (89.5 [73–133] vs 71.5 [56–104] mg/dL; P < .00005), non–high-density lipoprotein cholesterol (non-HDL-C; 128 [104–153] vs 107 [92–123] mg/dL; P < .00005), and triglycerides/HDL-C (2.2 [1.6–3.4] vs 1.7 [1.1–2.5] mg/dL; P = .0003) and lower levels of HDL-C (41 [36.5–47] vs 45 [37–53] mg/dL; P = .012). DS youth had higher high-sensitivity C-reactive protein, interleukin-6, small low-density lipoprotein particles (LDL-P), and total LDL-P, but similar LDL-P size. Youth with DS had less visceral fat (VFAT), fat mass, and lean mass for BMI z score, but greater VFAT at higher fat mass. However, VFAT did not fully explain the increased prevalence of dyslipidemia or prediabetes in youth with DS. CONCLUSIONS: Despite similar insulin resistance, youth with DS had greater prevalence of dyslipidemia and prediabetes than typically developing youth, which was not fully explained by VFAT.